Heraclitus, Rivers and Ecosystems - Robin Attfield (Studia Ecologiae et Bioethicae)
Heraclitus is interpreted not as holding that rivers exist only on a momentary basis, but as holding that the basis of their identity is problematic. The identity of rivers is discussed through examples, including cases where the identity of rivers depends on the inclusion of one or more of their tributaries, or of none at all. The family-resemblance approach cannot answer questions about the sameness of rivers, answers to which remain far from clear. This may seem unimportant, except that rivers are agreed to be ecosystems, which some hold to have a good of their own and therefore to have moral standing. But the loose nature of their identity, as articulated when the concept of ecosystem was introduced by Sir Arthur Tansley, belies this view. Besides, "the Amazon" matters (enormously) because it is an endangered regional system, liable to morph into a savannah, and thus to trigger a domino effect among other regional systems; this is quite different from an ecosystem consisting of one particular river (or part thereof), or even of its watershed.